Bryce Canyon & Zion National Parks [videorecording (DVD)] - Valentini, Chris; Paterson, William, 1919-2003 (Questar, 2003)
Examines the history, geology, wildlife, and flora of Utah's Bryce Canyon and Zion National Parks.